Back Cover Image, Volume 3, Number 3, July 2021. Issue 3 (28th July 2021) - Kang, Hui‐Ju; Lee, Tae‐Gyu; Kim, Heejin; Park, Jae‐Woo; Hwang, Hyun Jin; Hwang, Hyeonseok; Jang, Kwang‐Suk; Kim, Hae Jin; Huh, Yun Suk; Im, Won Bin; Jun, Young‐Si
Abstract : Back cover image : In article number 10.1002/cey2.116, Young‐Si Jun and co‐workers develop 3D carbon‐carbon nitride(C@CN) microspheres via molecular cooperative assembly, which then are utilized as a high‐loading sulfur‐host material by pelletizing in the lithium‐sulfur battery. Free‐standing electrode consisting of C@CN microspheres offers a new approach for scalable high‐energy dense sulfur electrodes.